The relationship between mid-upper arm circumference and blood pressure in Walter Sisulu University community - Wenzile S Mthethwa; Zuqaqambe M Mampofu; Madigoahle A Mokwena; Nthai E Ramoshaba (Blood Pressure)
Prevalence of hypertension is increasing to higher levels in South Africa. Anthropometric measures for obesity are well known to predict the development of hypertension. However, the relationship between mid-upper arm circumference (MUAC) and blood pressure (BP) is scant in South African communities such as universities. Therefore, this study was aimed at investigating the correlation between MUAC and BP among the community of Walter Sisulu University (WSU). A total of 230 participants from WSU (students and staff members), 113 females and 117 males aged ≥ 18 years participated in this cross-sectional study. MUAC, systolic BP (SBP) and diastolic BP (DBP) were measured using standard procedures. In a Pearson’s correlation analysis, MUAC was positively correlated with SBP and DBP in both women (SBP; r = 0.53, P< 0.001; DBP; r = 0.45 P < 0.001) and men (SBP; r = 0.29 P = 0.001; DBP; r = 0.25 P = 0.007). Furthermore, in the multivariable-adjusted regression analysis, MUAC was positively associated with SBP in women only (adjusted R2 = 0.489, β = 0.29 (95% CI = 0.16; 2.08)), P =0.023) after adjusted for age, body fat percentage, waist-to-height ratio, smoking and alcohol. MUAC is positively correlated with BP in women, not in men of WSU community. MUAC, as a simple and low-cost quantifiable parameter, could be employed as a risk indicator in the early detection and prevention of cardiovascular diseases (CVDs) in women.